2003
DOI: 10.2337/diabetes.52.10.2503
|View full text |Cite
|
Sign up to set email alerts
|

Nestin-Lineage Cells Contribute to the Microvasculature but Not Endocrine Cells of the Islet

Abstract: To clarify the lineage relationship between cells that express the neural stem cell marker nestin and endocrine cells of the pancreas, we analyzed offspring of a cross between mice carrying a nestin promoter/enhancer-driven cre-recombinase (Nestin-cre) and C57BL/ 6J-Gtrosa26 tm1Sor mice that carry a loxP-disrupted ␤-galactosidase gene (Rosa26). In nestin-cre ؉/tg ;R26R

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
89
1
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 45 publications
10
89
1
1
Order By: Relevance
“…4F,G) and of PC2 Ϫ/Ϫ , PC2 ϩ/ϩ , and Gcgr Ϫ/Ϫ mice (not shown) contained nestin ϩ cells that did not express hormones. These cells are likely to be the mesenchymal nestin ϩ cells described by others (Delacour et al, 2004;Esni et al, 2004;Humphrey et al, 2003;Klein et al, 2003;Lardon et al, 2002;Treutelaar et al, 2003).…”
Section: Reappearance Of Nestin Expression In Pancreatic Cells Of Adumentioning
confidence: 69%
See 1 more Smart Citation
“…4F,G) and of PC2 Ϫ/Ϫ , PC2 ϩ/ϩ , and Gcgr Ϫ/Ϫ mice (not shown) contained nestin ϩ cells that did not express hormones. These cells are likely to be the mesenchymal nestin ϩ cells described by others (Delacour et al, 2004;Esni et al, 2004;Humphrey et al, 2003;Klein et al, 2003;Lardon et al, 2002;Treutelaar et al, 2003).…”
Section: Reappearance Of Nestin Expression In Pancreatic Cells Of Adumentioning
confidence: 69%
“…This possibility was supported by the discovery of nestin ϩ cells in epithelial cells of the pancreatic bud of mouse embryos from e-10 to e-15 (Esni et al, 2004), raising the prospect that these cells were endocrine precursor cells. This possibility is controversial since several reports indicated that nestin expression was restricted to cells derived from the mesenchyme (Humphrey et al, 2003;Klein et al, 2003;Lardon et al, 2002;Selander and Edlund, 2002;Treutelaar et al, 2003). The derivation of pancreatic endocrine and exocrine cells from nestin precursors is further complicated by conflicting results obtained from cell lineage analysis of pancreatic cells using molecular marking techniques.…”
Section: Introductionmentioning
confidence: 99%
“…These studies require further confirmation, as other investigators found that nestin was a marker for non-endocrine cells. 47,48 Seaberg et al 49 reported clonal identification of multipotent pancreatic precursors from adult mouse pancreas that differentiate in vitro into both islet endocrine and neural lineages. Interestingly, these islet lineage clones display glucoseresponsive insulin secretion.…”
Section: Ex Vivo Conversion Of Cells Into Functional B-cellsmentioning
confidence: 99%
“…While nestin protein is robustly expressed in the developing CNSd in which it appears during the time of CNS stem and progenitor cell proliferation and neuronal migrationdit subsequently decreases as the brain develops (Lendahl et al, 1990;Tohyama et al, 1992;Dahlstrand et al, 1995;Kojima et al, 2004). Postnatal expression of nestin is limited to the brain subventricular (SVZ) zone and endothelial cells (Treutelaar et al, 2003;Mokry et al, 2004;Romanko et al, 2004;Ernst and Christie, 2005;Tonchev et al, 2005). Re-expression of nestin has recently been observed in activated astrocytes following various pathological conditions both in vitro and in vivo (Schmidt-Kastner and Humpel, 2002;Wei et al, 2002;Lang et al, 2004;Namba et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, even in normal development, there is emerging evidence that nestin is not exclusivley restricted to neural progenitor/stem cells, as its presence has been reported in multiple lineage-committed cell types, including cardiac muscle, lens-epithelial cells, multipotent pancreatic stem cells, Schwann cells, microglia cells and oligodendrocytes (Zimmerman et al, 1994;Yang et al, 2000;Vanderwinden et al, 2002;Treutelaar et al, 2003;Yokoyama et al, 2004;Amoh et al, 2005). In addition, nestin co-expression with early or late stage neuronal phenotypic markers, such as beta-tubulin-III and MAP-2, has also been reported at a certain stage of neuronal development (Rosser et al, 1997).…”
Section: Introductionmentioning
confidence: 99%